Variaciones en torno al tema de lo propio en el arte latinoamericano de los 50 años (1998)
In the early nineteen fifties, a greatdeal of attention was given to thediscrepanáes that arase regarding theidea of uniqueness as inherited fromthe advent of modernity. Nationalmodels had been exhausted and tapiessuch as acculturation and transculturationbegan to be vehemently discussed.W hat was critiázed was the m errepassive reception of that which carnefrom abroad, and instead, emphasiswas placed on the recovery of theunique, oriented by means of differentanalytical perspectt"ves. In the speáficfield of Fine arts there is a rupture notonly wt"th previous discourse, but alsowith the formal and thematic proposalsthat had prevailed in the firrsthalf of the century.